2022
DOI: 10.1590/fst.65521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold storage on shelf life of sour passion fruit progenies

Abstract: The present study aimed to evaluate the storage fruit potential of sour passion fruit progenies at temperatures of 7, 14 and 25 °C. The fruits were harvested at 30% yellow peel color, selected, sanitized and stored under refrigeration in chambers with relative humidity of 80% (± 5%) for a period of 12 days. The experiment was installed in a factorial scheme (3 × 3 × 4), with three progenies selected in the breeding program (P42, P45 and P49), three storage temperatures (7, 14 and 25 ° C) and four evaluation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…However, in other traits, such as weight loss, firmness, shrinkage and vitamin C content , the hypobaric method showed better results than cold storage. On the other hand, the cold storage affected the fruit appearance negatively, because it caused shrinkage in all the passion fruit germplasm (both 10 and 20 days after storage), which would be related to the dehydration (Nunes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in other traits, such as weight loss, firmness, shrinkage and vitamin C content , the hypobaric method showed better results than cold storage. On the other hand, the cold storage affected the fruit appearance negatively, because it caused shrinkage in all the passion fruit germplasm (both 10 and 20 days after storage), which would be related to the dehydration (Nunes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that passion fruit can be stored around 20 days at low temperatures (Manrique et al, 2020) because this method reduces respiration rates (i.e. CO 2 production) and ethylene production (Makule et al, 2022;Prasad and Mali, 2000), nevertheless the method promotes dehydration (Nunes et al, 2022). Both, ethylene and CO 2 production increased in all germplasm (Table 1), these variables did not show statistical differences between the hypobaric and cold storage; however, the amount of these gases produced in the low temperature storage methods (hypobaric and cold storage) was lower than that produced by preserving the fruit in the environment temperature for all the evaluated passion fruits.…”
Section: Storage Time (Days)mentioning
confidence: 99%
“…3 Brazil is the largest producer and consumer of yellow passion fruit (Passiflora edulis), producing 593 429 tons in a planted area of 41 584 ha in 2019. 6 Most of this production is destined for the juice industry, which generates a large amount of waste, such as peels and seeds, which are generally not reused. 7 These residual seeds from the juice production process are rich in oil, representing about 30% of their composition, 8 besides being considered good sources of essential fatty acids, ⊍-linolenic acid (LNA; 18:3n) and linoleic acid (LA; 18:2n-6).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is the largest producer and consumer of yellow passion fruit ( Passiflora edulis ), producing 593 429 tons in a planted area of 41 584 ha in 2019 6 . Most of this production is destined for the juice industry, which generates a large amount of waste, such as peels and seeds, which are generally not reused 7 …”
Section: Introductionmentioning
confidence: 99%